Multivariate analysis in pollen parent (restorer line) of hybrid rice (Oryza sativa I.) (Bangladesh Journal of Plant Breeding and Genetics, 2011)
Bangladesh Journal of Plant Breeding and Genetics, Vol.22(2) December 2009 63-66